A new structural motif for cadmium dithiocarbamates: crystal structures and Hirshfeld surface analyses of homoleptic zinc and cadmium morpholine dithiocarbamates - Ahmad, Jimmy; How, Fiona N.-F.; Halim, Siti Nadiah Abdul; Jotani, Mukesh M.; Lee, See Mun; Tiekink, Edward R.T. (De Gruyter, 2019)
The crystal and molecular structures of two homoleptic morpholine-derived dithiocarbamates of zinc, binuclear {Zn[S 2 CN(CH 2 CH 2 ) 2 O) 2 ] 2 } 2 (1), and cadmium, one-dimensional coordination polymer {Cd[S 2 CN(CH 2 CH 2 ) 2 O) 2 ] 2 } 2 (2), are described. In 1, a centrosymmetric binuclear molecule is found as there are equal numbers of chelating and bidentate bridging dithiocarbamate ligands; weak transannular Zn···S interactions are found within the resultant eight-membered {···SCSZn} 2 ring which has the form of a chair. The resultant 4+1 S 5 donor set is highly distorted with the geometry tending towards a square-pyramid. By contrast, a square-planar geometry is found in centrosymmetric 2 defined by symmetrically chelating dithiocarbamate ligands. The presence of Cd···S secondary bonding in the crystal of 2 leads to a distorted 4+2 S 6 octahedron and a linear coordination polymer, which is unprecedented in the structural chemistry of cadmium dithiocarbamates. The analyses of the Hirshfeld surfaces for 1 and 2 show the dominance of H···H, S···H/H···S and O···H/H···O contacts to the surface, i.e. contributing around 90 and 80%, respectively. © 2019 Walter de Gruyter GmbH, Berlin/Boston.